Long-term change in the depth of seasonally frozen ground and its ecohydrological impacts in the Qilian Mountains, northeastern Tibetan Plateau - Qin, Yue; Lei, Huimin; Yang, Dawen; Gao, Bing; Wang, Yuhan; Cong, Zhentao; Fan, Wenjie (Journal of Hydrology, 2016)
Changes in seasonally frozen ground at high elevations under the effects of global warming and their ecohydrological impacts are important for understanding changes in regional water resources and ecosystems. This study estimates the spatio-temporal variability in the maximum thickness of seasonally frozen ground (MTSFG) in the Qilian Mountains in the northeastern Tibetan Plateau from 1960 to 2014 by using a variant of the Stefan solution. The present study analyzes changes in streamflow and vegetation to reveal the ecohydrological impacts of changes in the MTSFG. Results indicate that the MTSFG shows a mean decreasing trend of 7.4 cm/10a in the past 55 years in correspondence to the significantly increasing air temperature (0.34 degrees C/10a). The greatest decreasing trend of the MTSFG is at elevations of 3400-3800 m. The annual baseflow has increased significantly in most of the sub-basins for which the increasing precipitation is the main factor. The MTSFG is another major factor for the increase in baseflow during the cold season (from November to April) according to the results of gray relational analysis. The leaf area index (LAI) during the growing season has increased by 0.045/10a since 2000, and the start of growing season has advanced by 1.8-2.1 d/10a at elevations of 3000-3800 m, where the vegetation cover is the densest. Furthermore, results of correlation analysis show that the topsoil moisture increases with the MTSFG decreases. Results of gray relational analysis show that the decrease in MTSFG is the main reason for the advancing green-up dates and increasing LAI in the initial period of the growing season. Our results show that the ecohydrological processes are changing along with frozen soil degradation in the northeastern Tibetan Plateau. (C) 2016 Elsevier B.V. All rights reserved. National Natural Science Foundation of China (NSFC) [91225302, 91425303] SCI(E) ARTICLE 204-221 542